Pengaruh Model Inside Outside Circle terhadap Hasil Belajar Matematika Kelas III SD Swasta Pab 5 Klumpang - Hadi Widodo; Syahrina Anisa Pulungan; Cindy Pradina (Educational Consultant & Counseling Career (EC3) Mataram, 2024)
This research aims to determine the effect of the model Inside Outside Circle on mathematics learning outcomes in class III of SD Swasta Pab 5 Klumpang. This research involved two class, namely the experimental class and the control class. The sample for this research was class III SD Swasta Pab 5 Klumpang. This research instrument is a multiple choice test with a total of 20 questions. Data analysis was taken from the pre test and post test, apart from that data analysis was carried out for normality tests, homogeneity tests, reliability tests, and undependent samples t tests. The results of the research show that: (1) The result of the reliability test of mathematics learning outcomes data using the model Inside Outside Circle received a sig value of 0,633>0,05, (4) The result of the t test (hypothesis test) using the model Inside Outside Circle the mathematics learning outcomes data received a sig value of 0,000<0,05. From this data it can be concluded that there is an influence of the model Inside Outside Circle on mathematics learning outcomes.